Performance Analysis of Amplify and Forward Cooperative Networks over Rayleigh and Nakagami-m Channels based Relaying Selection - Mohammed, Ali Abdulwahhab; Yu, Li; Yu, Li; Al-Kali, Manar; Al-Kali, Manar; Wang, Desheng; Wang, Desheng (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2016)
In this paper investigates the performance, analysis of amplify and forward (AF) cooperative networks with the relay selection over Nakagami-m and Rayleigh fading channels and M-ary phase shift keying (MPSK) modulations. New closed form expressions are derived for the general cases of Rayleigh and Nakagami-m fading channels. cumulative density function (CDF), probability density function (PDF) of the end –to - end signal –to – nois ratio (SNR) of a dual-hop opportunistic AF relaying system, moment generating function (MGF), symbol error rate (SER) and outage probability (Pout). and the first closed-form study for opportunistic AF relaying system where the best node is selected from a number of candidate intermediate nodes to relay the data signal between the source and the destination. Simulation results reveal that the PDF , CDF, Pout and SER performance downgrades either the m parameter or the number of relays increases. Our simulations compared between Rayleigh and Nakagami-m links for a different number of relays. In addition, different modulation techniques are examined to show the effect of the modulation scheme which was used over Rayleigh and Nakagami-m fading channels on the cooperative networks. The obtained results proved the impact of m parameters, relay selection and modulation index on the pout and SER performance.